Monocular Diplopia in Astigmatism and Traumatic Iridodialysis Patient: A Case Report - Pranata, Andra; Wahyuni, Indri; Hermawan, Dicky (Journal of Neonatal Surgery, 2025)
Monocular diplopia is the perception of double (or many) pictures while seeing with just one eye, and it reflects an ocular rather than a brain origin. Only 11% patients identified as monocular diplopia. Cataracts, corneal surface abnormalities (such as keratoconus or astigmatism), and, in rare cases, occipital cortex lesions can all cause monocular diplopia. We report a case of monocular diplopia patient caused by either astigmatism or traumatic iridodialysis. A 43-year-old man complained of double vision, nausea, and vomiting while utilizing two eyes or when patient’s occluded left eye was opened. In left eye, the patient had astigmatism and traumatic iridodialysis. Patient’s left eye was occluded following penetrating injury in January 2022 and had iris repositioning and corneoscleral suturing. On examination, the left eye showed conjunctival hyperemia, temporal mild subconjunctival hemorrhage, corneoscleral suture at 3 o'clock, corneal conjunctivalization and traumatic iridodialysis. The other tests were normal. Monocular diplopia was detected in the patient. Diplopia is one of the symptoms indicating the iris has to be repaired, particularly after trauma. The reconstruction will help patients by reducing diplopia, photophobia, and glare while preserving visual acuity. As iris restoration remains a subject of innovation in ophthalmology, several studies were necessary to optimize the method and identify widespread side effects.Ocular problems are the most prevalent etiology for monocular diplopia, including astigmatism and traumatic iridodialysis. Careful examination to determine the etiology is important since treating underlying cause remains the mainstay treatment for monocular diplopia